2014
DOI: 10.1002/dta.1679
|View full text |Cite
|
Sign up to set email alerts
|

Determination of GHB in human hair by HPLC‐MS/MS: Development and validation of a method and application to a study group and three possible single exposure cases

Abstract: Gamma-hydroxybutyrate (GHB) over the last two decades has generated increased notoriety as a euphoric and disinhibiting drug of abuse in cases of drug-related sexual assault and for this reason it is considered a 'date rape' drug. The first aim of this paper was to develop and fully validate a method for the detection of GHB in human hair by high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) after liquid-liquid extraction (LLE). The second aim was the application of the method to hair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 13 publications
3
40
0
Order By: Relevance
“…The GHB range was <0.32-1.00 ng/mg hair in controls, with 0.32 ng/mg representing LOQ. Other investigators have reported higher values, including Goullé et al (2003), 0.32-1.86 ng/mg, n ¼ 61; Bertol et al (2015), 0-5.09 ng/mg, n ¼ 30; and Shi et al (2016), 0.28-4.91 ng/ mg, n ¼ 66. Statistical analysis of GHB concentrations in hair employed the Spearman rank order correlation for nonparametric data, with a post-hoc Bonferroni analysis employing a standard two-way t-test.…”
Section: Patient Samples and Methodological Approachmentioning
confidence: 80%
“…The GHB range was <0.32-1.00 ng/mg hair in controls, with 0.32 ng/mg representing LOQ. Other investigators have reported higher values, including Goullé et al (2003), 0.32-1.86 ng/mg, n ¼ 61; Bertol et al (2015), 0-5.09 ng/mg, n ¼ 30; and Shi et al (2016), 0.28-4.91 ng/ mg, n ¼ 66. Statistical analysis of GHB concentrations in hair employed the Spearman rank order correlation for nonparametric data, with a post-hoc Bonferroni analysis employing a standard two-way t-test.…”
Section: Patient Samples and Methodological Approachmentioning
confidence: 80%
“…In the same year, Bertol et al [16] reported that, due to sweat contamination, GHB concentration in the first 0.5 cm hair segment of a group of non-consumers was statistically higher in comparison to all the other subsequent segments where mean GHB concentration was 1.27 ± 0.73 ng/mg.…”
Section: Ghb Endogenous Levels In Hairmentioning
confidence: 99%
“…Of the 2304 sources found, only 20 [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] were considered appropriate for the purpose of this paper. A flowchart of the selected papers and inclusion criteria are reported in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations